A 3D Bioengineered Model of Intestinal Immunity - Paul, Harry Theodore (Tufts Archival Research Center, 2019)
Throughout the intestine, clumped in the area of the epithelium that covers the highly immunologic Peyer’s patches, there is a rare cell type that determines which pathogens should be passed on to Peyer’s patch lymphocytes. Known as Microfold, or “M” cells, these epithelial cells have unique recognition and phagocytosis functions like those of immune cells and are heavily implicated in current biomedical questions of human pathophysiology. In this work, we present the first 3D model of M cells. The process of designing and evaluating this model revealed convincing evidence that M cell induction is not a simple nor a binary process. RANKL induction, which resulted in significant M-cell associated genetic changes, was not able to induce M cells in the Caco-2 model, nor strong GP2 presentation, in many enteroid cultures. The frequently cited Raji B cell induction resulted in GP2 expression on the wrong side of organoids, induced phagocytosis on monolayers, and disrupted the epithelial integrity of 3D models. These stem cell-derived M cell models: of organoids, 2D monolayers, and 3D scaffolds, may be a significant step forward in closing the gap between the basic cell biology and previously created models.